The Oromo Movement: The Effects of State Terrorism and Globalization in Oromia and Ethiopia - Jalata, Asafa (Social justice, 2017)
This essay critically explores the dialectical relationships between the Oromo national movement and the consequences of state terrorism and globalization in Oromia and Ethiopia. On one side, the Oromo people are struggling to empower themselves and gain control on their economic and cultural resources; on the other side, with the help of global powers and their international institutions the Ethiopian government is engaging in state terrorism and massive human rights violations, transferring Oromo economic resources (particularly land) to state elites and their global partners. Opposing such policies, the ongoing Oromo peaceful protest movement is taking the Oromo struggle to a new level and transforming the relationship between the Oromo and the Ethiopian state.